Relationship between isometric hip torque with three kinematic tests in soccer players - Rodrigues, G.; Dias, A.; Ribeiro, D.; Bertoncello, D. (Physical Activity and Health, 2020)
Introduction: Hip muscle strength has a good component to improve the execution of movement preventing excessive knee movements, such as dynamic valgus, which is a factor related to ACL injuries, however, the relationship between isometric torque and dynamic valgus is not yet well established. Functional tests that resemble sports have been used for movement analysis and possible injury minimizing factor.